Klinički značaj biomarkera koagulacije u terapiji venskog pritiska za sprečavanje duboke venske tromboembolije donjih ekstremiteta: meta-analiza: Coagulation Biomarkers in Venous Pressure Therapy - Niu, Jingrong; Zhou, Shuang; Zhang, Lijin; Li, Chunmin; Ren, Hualiang (Journal of Medical Biochemistry, 2025)
Background: To evaluate the biochemical and clinical significance of venous pressure therapy in preventing venous thromboembolism (VTE) through analysis of coagulation and fibrinolysis biomarkers, including fibrinogen (FIB), D-dimer (D-D), and activated partial thromboplastin time (APTT). Methods: Randomized controlled trials published between 2013 and 2025 were systematically retrieved from PubMed, CNKI, VIP, and Wanfang databases. Eligible studies investigated venous pressure therapy and reported coagulation-related indices. Pooled effect sizes were calculated for key biochemical markers (FIB, D-D, APTT, PT, TT) and venous hemodynamic outcomes. Results: Nineteen clinical studies met inclusion criteria. Meta-analysis revealed that venous pressure therapy significantly reduced plasma FIB and D-D levels, prolonged APTT, prothrombin time (PT), and thrombin time (TT), and improved venous blood flow velocity. These changes reflect improved anticoagulant activity, enhanced fibrinolysis, and reduced risk of thrombosis. Importantly, the observed modulation of biochemical markers correlated with a lower incidence of lower-extremity deep venous thrombosis. Conclusion: Venous pressure therapy favorably alters coagulation and fibrinolytic biomarkers, underscoring their diagnostic value in monitoring therapeutic efficacy and thrombotic risk. These findings highlight the critical role of laboratory indices in guiding the prevention and management of VTE, supporting their integration into standardized clinical practice.